Implementation of Gender-Equitable Education in shaping children's character based on Nggusuwaru Local Wisdom to realize a Women-Friendly Environment and care for children - Nurbayan, ST; Nurhasanah, Nurhasanah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
An abstranct is a brief summary of a research  article, thesis, review, conference  proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry  for any given academic  paper or patent application.  Absatrcting  and indexing services for various  academic  discipline  are aimed  at compiling  a body of literature  for that  particular  subject. Abstract length varies by discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper.